Clustering of Symbolic Data based on Affinity Coefficient: Application to real data sets - Sousa, Áurea (2014)
6th Workshop on Statistics, Mathematics and Computation-3rd Portuguese-Polish Workshop on Biometry (6thWSMC and 3rdPPWB), July 3-4, 2012, Universidade da Beira Interior, Covilhã, Portugal (Comunicação).